Strategi Pengoptimalan Kekuatan Media Sosial Instagram Dalam Usaha Bancreps - Uswatun Hasanah; Zakiyah Zahara; Ira Nuriya Santi; Juliana Kadang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The digital transition in various fields including the economy, provides opportunities for MSMEs to conduct research on marketing strategies that are now being developed to participate in the transformation of the marketing economy. Social media is often utilized to increase brand awareness, and even support business growth. Instagram is the most popular social media platform utilized by business owners to promote their products. The research methodology used in this research is a qualitative research design that produces descriptive data. The data collection method of this research is by conducting observations, interviews, and documentation. A business must implement a marketing strategy to ensure that their marketing activities are successful, this is the most important aspect of a marketing strategy. The results of interviews conducted directly show that the digital marketing strategy implemented by Bancreps has succeeded in increasing user satisfaction on Instagram. The digital marketing strategy implemented by Bancreps includes planning, implementing, and monitoring to increase sales of the company's products.